Virtual room decorator in android - Nurul Ain, Ahmed (2012)
This thesis deals with usability assessment for a mobile-emulator of virtual reality environment for room decorating application in Android platform titled,Virtual Room Decorator(VRD)in Android Application,which is it consists of the overview of proposed project, perception of the planetary surface,techniques will use to create the 2D/3D models and its database restoration.I wish to build a high quality database of room decorating scenes,along with its real-world three dimensional (3D) viewer.Such a database is useful for a variety of applications,including training systems for object detection and validation of 3D output. Also provides a simulation mobile platform to test and validate different rover chassis design,its navigation and locomotion algorithms,and the support rover operation for the application built.Besides,the comparison with the various related current systems and applications in the web browser and usability of popular mobile application platforms also issued here.